Protective Effect of Melatonin on LPS-stimulated Granulosa Cells in Japanese Quail - Guang-Min Yu; Naoki Isobe; Teruo Maeda (The Journal of Poultry Science, 2017)
The aim of this study was to evaluate the potential of melatonin to protect cultured granulosa cells from the harmful effects of lipopolysaccharide (LPS) in quail. Granulosa cells isolated from Japanese quails were pretreated with or without melatonin (10 or 100 μg/mL) for 12 h and then incubated for 12 h in the absence or presence of 100 ng/mL LPS. The expression of pro-inflammatory cytokines and chemokine was detected by quantitative real-time PCR. The levels of oxidative stress biomarkers (dityrosine and nitrite) were determined by ELISA and the Griess reaction. Cell viability was quantified using an MTT assay. Additionally, the level of progesterone was measured by ELISA. We found that melatonin decreased LPS-induced expression of IL-1β, IL-6, and IL-8. In addition, melatonin increased the dityrosine level, but suppressed the nitrite level. Finally, melatonin administration increased the viability of LPS-stimulated granulosa cells in vitro. However, progesterone basal secretion was not significantly changed. These results suggest that melatonin protects cultured granulosa cells from LPS-induced inflammatory and oxidative stress damage and provide evidence that melatonin might have therapeutic utility in ovarian follicle infection in Japanese quail.